Aural comprehension in young learners' FL development - Mihaljević-Djigunović, Jelena (Array, 2012)
While research on listening as a FL skill has traditionally been product-oriented, recent studies (e.g., Goh, 2002 ; Vandergrift, 2007) have investigated aural comprehension processes in FL learning in terms of constructing and communicating meaning. In early FL learning listening provides the basic input for literacy development: it is through oral language that the foundation for learning a new language is established. This contribution describes a longitudinal study on the development of aural comprehension skills in English as a FL of Croatian and Italian young learners. The study is part of a seven-country project investigating early language learning in Europe. The authors hypothesised that early aural development would be characterised by individual differences among learners. The sample included 92 learners who were followed for four years. Each year participants’ aural comprehension was measured by listening tasks of increasing linguistic and cognitive complexity. The tasks required learners to identify specific words, comprehend language chunks and relate them to a communicative context illustrated in sets of pictures. Results were considered against information collected by a post-listening questionnaire. Findings provide evidence of individual differences among young learners related to differences in their attitudes, exposure to English in and out of class, and home support.